Enabling leadership promotes a positive working climate - Parkkila, Paula (2013)
This study looks for current information about factors related to educational leadership that help to promote a positive working climate and which may ultimately influence the employees' overall well-being at work. The study focuses on finding out what is the role of open interaction for the development of a positive working climate. Crucial information about well-being promoting leadership practices is needed in the Finnish context. Previous research shows that employees' experiences of well-being at work in educational organizations vary. Promoting employee well-being has become a crucial leadership issue in the Finnish society. Leadership training has been found to have a key position in promoting well-being at work. However, the current training seems not to equip leaders to deal with well-being issues well enough. Research evidence supports the need to develop leadership in Finnish educational organizations especially with skills to do with leading people through interaction and managing personal relations. The main interest in the study is in the employees' views and interpretations on leadership practices promoting well-being at work. The study followed a qualitative case study approach. Six lecturers teaching in five degree programs representing different occupational fields in one Finnish university of applied sciences formed the case. The case organization represents vocational higher education, which is a suitable context providing information about leadership practices promoting well-being at work. The data were collected using a semi-structured interview as the data collection method. The data gathered in the interviews were analyzed using a qualitative inductive data-driven content analysis. The key findings gathered in three summary tables introduce factors essential for well-being in a work community. They provide a view about understanding good leadership as an enabling whole. This leadership approach relies on open interaction, an open discussion culture and reciprocity between leaders and employees. Enabling leadership practices in the educational context promote both the job satisfaction, the working climate and, in the end, well-being at work. These leadership practices help to explain the development of a positive working climate. Open and appreciating interaction is considered an essential factor promoting the development of a good working climate. To sum up, co-working, group spirit and interaction are preconditions for a positive working climate. The findings support the current demands for developing leadership training in Finland to better equip leaders with skills that help to promote interaction and, thus, well-being at work.